Discourse Analysis on Multicultural Society Perception towards the Harmony of Inter-Tribal Marriages in Lamasi District, Luwu Regency - Ilmy Amaliyah; Mustaming; Rahmawati (Universitas Islam Negeri Palopo, 2025)
This study examines the discourse surrounding multicultural society's perception of inter-tribal marriages in Lamasi District, Luwu Regency, through a discourse analysis lens. As Indonesia represents a diverse archipelago with numerous ethnic groups, inter-tribal marriages serve as crucial indicators of social integration and cultural harmony. This research investigates how community members in Lamasi District construct and articulate their views on marriages across tribal boundaries, exploring the tensions between traditional cultural preservation and modern multicultural coexistence. The study employs critical discourse analysis to examine verbal and written communications among community members, religious leaders, traditional authorities, and married couples themselves. Data collection encompasses in-depth interviews, focus group discussions, and analysis of public discourse in community settings. The analysis reveals complex negotiations between maintaining cultural identity and embracing diversity, highlighting both acceptance and resistance patterns within the multicultural framework of Lamasi District. Findings indicate that perceptions of inter-tribal marriages are shaped by multiple factors including generational differences, educational background, economic considerations, and religious interpretations. While younger generations demonstrate greater openness toward cross-cultural unions, traditional community structures continue to influence marriage decisions significantly. The research identifies specific discourse patterns that either promote harmonious integration or reinforce tribal boundaries, providing insights into the mechanisms through which multicultural societies navigate cultural diversity. This study contributes to understanding how discourse shapes social attitudes in multicultural contexts and offers implications for promoting social cohesion in diverse Indonesian communities. The findings may inform policy development and community programs aimed at fostering inclusive multicultural societies while respecting cultural heritage.